DETERMINING THE HUBBLE CONSTANT FROM HUBBLE PARAMETER MEASUREMENTS - Chen, Y.; Kumar, S.; Ratra, Bharat (My University, 2017)
We use 28 measurements of the Hubble parameter, H(z), at intermediate redshifts 0.07 <= z <= 2.3 to determine the present-day Hubble constant H-0 in four cosmological models. We measure H-0 = 68.3(-2.6)(+2.7), 68.4(-3.3)(+2.9), 65.0(-6.6)(+6.5) and 67.9(-2.4)(+2.4) km s(-1) Mpc(-1) (1 sigma errors) in the Lambda CDM (spatially flat and non-flat), omega CDM, and phi CDM models, respectively. These measured H-0 values are more consistent with the lower values determined from recent data on the cosmic microwave background and baryon acoustic oscillations, as well as with the value found from a median statistical analysis of Huchra's compilation of H-0 measurements, but include the higher local measurements of H-0 within the 2 sigma confidence limits.
Citation: Chen, Y., Kumar, S., & Ratra, B. (2017). DETERMINING THE HUBBLE CONSTANT FROM HUBBLE PARAMETER MEASUREMENTS. Astrophysical Journal, 835(1), 4. doi:10.3847/1538-4357/835/1/86
Keywords: Cosmological Parameters; Dark Energy; Deceleration-Acceleration Transition; Luminous Red Galaxies; Dark; Energy